Oxidative Photocyclization of Aromatic Schiff Bases in Synthesis of Phenanthridines and Other Aza-PAHs - Kos, Martin; Žádný, Jaroslav; Storch, Jan; Církva, Vladimír; Cuřínová, Petra; Sýkora, Jan; Císařová, Ivana; Kuriakose, Febin; Alabugin, Igor V (International journal of molecular sciences, 2020)
The oxidative photocyclization of aromatic Schiff bases was investigated as a potential method for synthesis of phenanthridine derivatives, biologically active compounds with medical applications. Although it is possible to prepare the desired phenanthridines using such an approach, the reaction has to be performed in the presence of acid and TEMPO to increase reaction rate and yield. The reaction kinetics was studied on a series of substituted imines covering the range from electron-withdrawing to electron-donating substituents. It was found that imines with electron-withdrawing substituents react one order of magnitude faster than imines bearing electron-donating groups. The 1H NMR monitoring of the reaction course showed that a significant part of the Z isomer in the reaction is transformed into E isomer which is more prone to photocyclization. The portion of the Z isomer transformed showed a linear correlation to the Hammett substituent constants. The reaction scope was expanded towards synthesis of larger aromatic systems, namely to the synthesis of strained aromatic systems, e.g., helicenes. In this respect, it was found that the scope of oxidative photocyclization of aromatic imines is limited to the formation of no more than five ortho-fused aromatic rings.
Keywords: Photochemical Processes; Cycloaddition Reaction; imines; Phenanthridines; oxidace-redukce; fenantridiny; cykloadiční reakce; Schiffovy báze; Schiff Bases; Schiff bases; Oxidation-Reduction; Oxidants, Photochemical; azahelicenes; fotochemické oxidanty; fotochemické procesy; photocyclization; phenanthridines